2011
DOI: 10.1038/bjc.2011.143
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of GSTP1 promoter methylation in body fluids may complement PSA screening: a meta-analysis

Abstract: Background:Prostate-specific antigen (PSA) screening has low specificity. Assessment of methylation status in body fluids may complement PSA screening if the test has high specificity.Method:The purpose of this study was to conduct a meta-analysis of the sensitivity and specificity for prostate cancer detection of glutathione-s-transferase–π (GSTP1) methylation in body fluids (plasma, serum, whole blood, urine, ejaculate, and prostatic secretions). We conducted a comprehensive literature search on Medline (Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 28 publications
(106 reference statements)
3
80
0
Order By: Relevance
“…A recent meta-analysis of 22 manuscripts indicated good specificity (89%) but modest sensitivity (52%) of GSTP1 differential methylation for PCA screening [81]. The detection of hypermethylated DNA is also an adverse prognostic marker: RASSF1A, RARB2, and GSTP1 hypermethylation were correlated with the Gleason score and the serum PSA [82].…”
Section: Prostate Cancermentioning
confidence: 99%
“…A recent meta-analysis of 22 manuscripts indicated good specificity (89%) but modest sensitivity (52%) of GSTP1 differential methylation for PCA screening [81]. The detection of hypermethylated DNA is also an adverse prognostic marker: RASSF1A, RARB2, and GSTP1 hypermethylation were correlated with the Gleason score and the serum PSA [82].…”
Section: Prostate Cancermentioning
confidence: 99%
“…The pooled specificity for all included studies was 0.91 (95% CI: 0.82-0.95), and the pooled sensitivity was 0.78 (95% CI: 0.63-0.88). For the traditional biomarker, the sensitivity of PSA varied, but the specificity was generally low at about 20%, 32,54 which suggested that the APC methylation test has a much higher specificity than the PSA test. There was no evidence of publication bias (P ¼ 0.33).…”
Section: Characteristicsmentioning
confidence: 99%
“…All data used a log-odds scale (eg, for specificities, the effect size used was log (Spec/(1-Spec)). 32 Finally, due to the heterogeneity between studies, we performed the Cochrane Q test of heterogeneity for each analysis (based on deviations of observed log-odds from the common log-odds). The analyses were conducted using Stata 9.0 (Stata Corporation, College Station, TX, USA), and all P-values were two-tailed.…”
Section: Roc Analysismentioning
confidence: 99%
“…In the finding genes of this pathway, CYP3A4 and CYP3A5 expression is related to androgen metabolism (Rebbeck et al, 2008). Meta-analysis studies show that measurement of GSTP1 promoter methylation in plasma, serum, or urine samples may complement PSA screening for prostate cancer diagnosis (Wu et al, 2011).…”
Section: Metabolism Pathwaysmentioning
confidence: 99%